ANALYSIS OF NESTED TYPE INTEGRATED LEARNING MODEL IN INDONESIAN LANGUAGE LEARNING IN GRADE VI OF ELEMENTARY SCHOOL - Kiki Fajariani (CV Naskah Aceh, 2024)
This study analyzes the effectiveness of the Nested type integrated learning model in improving the Indonesian language skills of grade VI students at SD 1 Bireuen. Using a qualitative case study approach, data were collected through observation, interviews, and document analysis. The results showed that the Nested model significantly improved students' listening, speaking, reading, and writing skills. The integrated approach allows students to relate various aspects of language learning, thus creating a richer and more meaningful learning experience. This study confirms the potential of the Nested model as an innovative and effective teaching strategy in language education in elementary schools.